Extrahepatic biliary obstruction secondary to metastatic esophageal squamous cell carcinoma: An unusual presentation of Courvoisier's law. Issue 10 (28th October 2021) - Atiba, Kafi; Ramdass, Michael; Oladiran, Adedapo; Rahman, Muhammad
Abstract: Courvoisier's law states, "In the presence of jaundice and a palpable bladder, the cause is unlikely to be due to stone". Although esophageal squamous carcinoma is known to spread to celiac nodes, there is no description in the literature with it presenting and mimicking the above findings in Courvoisier's Law. Abstract : Courvoisier's law states, "In the presence of jaundice and a palpable bladder, the cause is unlikely to be due to stone". Although esophageal squamous carcinoma is known to spread to celiac nodes, there is no description in the literature with it presenting and mimicking the above findings in Courvoisier's Law.